1993
DOI: 10.1080/00220389308422272
|View full text |Cite
|
Sign up to set email alerts
|

Exchange rate policy and price level changes: Casualty tests for Turkey in the post‐liberalisation period

Abstract: The purpose of the present study is to examine the relationship between exchange rate changes and price level changes in Turkey during the 1980s using some modified Granger causality tests. During this period, Turkish exchange rate policy was characterised by considerable flexibility, in contrast to the long-standing policy of fixing the exchange rate until a foreign exchange crisis necessitated devaluation. The weight of the evidence presented suggests that Granger causality runs from price level changes to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1
5

Year Published

1995
1995
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
1
7
1
5
Order By: Relevance
“…These results imply not only that equities are an important additional factor to include in portfolio balance models of the exchange rate, but also suggest that the impact of equities is more important than the impact of government bonds and money. Rittenberg (1993) employed the Granger causality tests to examine the relationship between exchange rate changes and price level changes in Turkey. Since causality tests are sensitive to lag selection, therefore he employed three different specific methods for optimal lag selection [i.e, an arbitrarily selected, Hsiao method (1979), and the SMAR or subset model auto regression method of Kunst and Marin (1989)].…”
Section: Previous Empirical Studiesmentioning
confidence: 99%
“…These results imply not only that equities are an important additional factor to include in portfolio balance models of the exchange rate, but also suggest that the impact of equities is more important than the impact of government bonds and money. Rittenberg (1993) employed the Granger causality tests to examine the relationship between exchange rate changes and price level changes in Turkey. Since causality tests are sensitive to lag selection, therefore he employed three different specific methods for optimal lag selection [i.e, an arbitrarily selected, Hsiao method (1979), and the SMAR or subset model auto regression method of Kunst and Marin (1989)].…”
Section: Previous Empirical Studiesmentioning
confidence: 99%
“…Besides, Sever and Mızrak (2007) inform us that fluctuations in the exchange rate have an important effect on the domestic inflation and interest rates in Turkey. Rittenberg (1993) in his study, on the Turkish economy after 1980, determined that there is a one-way relationship from inflation to the exchange rate. He found that the devaluations seen after 1980 were not the main determinant of domestic prices, and that inflation was effective in the formation of the exchange rates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bu çalışmaların analiz dönemleri, frekansları farklı olduğu gibi bulguları da farklılıklar göstermektedir. Çeşitli dönemler ve farklı ülkeler için yapılan Granger nedenselliği analizleri sonucunda çift yönlü nedensellik bulgusuna ulaşanlara Koldhy ve Sohrabian (1990) (Almanya ve Japonya için), Altınay (1996), Nourzad (1997), Tarı (1997), Siregar (1999) (alt dönemler için), Maswana (2006) ve Güven ve Uysal(2013); döviz kurundan enflasyona tek yönlü nedensellik bulgusuna ulaşanlara Kholdy ve Sohrabian (1990) (Kanada için), Manning ve Andrianacos (1993), Fisunoğlu ve Çabuk (1998), Koch, Rosensweig ve Witt (1998), Mihaljek ve Klau (2001), Koç ve Abasız (2002), Telatar ve Telatar (2003), Gül ve Ekinci(2006) ve Yanar (2008); enflasyondan (fiyat değişmeleri) döviz kuruna tek yönlü nedensellik bulgusuna ulaşanlara ise Man-ning ve Andrianacos (1993), Rittenberg (1993), Rahman, Mustafa ve Bailey (1996), Terzi ve Zengin(1996), Kim (1998), Siregar (1999) (tüm dönem için) örnek olarak verilebilir. Agayev(2011) ise Azerbaycan için yaptığı analizler sonrasında bu iki değişken arasında eştümleşmenin ve nedenselliğin olmadığı bulgusuna ulaşmıştır.…”
Section: Konunun Neden Seçi̇ldi̇ği̇ Ve Oluşturulan Varsayimlarunclassified